The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1096/fj.202200419rr
|View full text |Cite
|
Sign up to set email alerts
|

Activation of FMS ‐like tyrosine kinase 3 protects against isoprenaline‐induced cardiac hypertrophy by improving autophagy and mitochondrial dynamics

Abstract: FMS-like receptor tyrosine kinase 3 (Flt3) expression was reported to increase in the heart in response to pathological stress, but the role of Flt3 activation and its underlying mechanisms remain poorly elucidated. This study was designed to investigate the role of Flt3 activation in sympathetic hyperactivity-induced cardiac hypertrophy and its mechanisms through autophagy and mitochondrial dynamics. In vivo, cardiac hypertrophy was established by subcutaneous injection of isoprenaline (6 mg/kg•day) in C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…SIRT1 activates downstream effectors of peroxisome proliferator-activated receptor γ coactivator 1-α (PGC-1α) and fibroblast growth factor 21 (FGF21) to promote autophagy [ 33 ]. Additionally, SIRT1 promotes transcription factor EB (TFEB) nuclear translocation and deacetylation, thereby activating the p53 and PI3K/AKT signaling pathways to promote autophagy and maintain mitochondrial dynamics balance [ 19 , 34 ]. During endoplasmic reticulum stress (ERS), SIRT1 expression is suppressed, and autophagy decreases.…”
Section: Regulation Of Cardiovascular Autophagy By Various Sirtuinsmentioning
confidence: 99%
See 2 more Smart Citations
“…SIRT1 activates downstream effectors of peroxisome proliferator-activated receptor γ coactivator 1-α (PGC-1α) and fibroblast growth factor 21 (FGF21) to promote autophagy [ 33 ]. Additionally, SIRT1 promotes transcription factor EB (TFEB) nuclear translocation and deacetylation, thereby activating the p53 and PI3K/AKT signaling pathways to promote autophagy and maintain mitochondrial dynamics balance [ 19 , 34 ]. During endoplasmic reticulum stress (ERS), SIRT1 expression is suppressed, and autophagy decreases.…”
Section: Regulation Of Cardiovascular Autophagy By Various Sirtuinsmentioning
confidence: 99%
“…Insufficient autophagy during heart failure is associated with impaired SIRT1/PGC-1α and AMPK signaling, as well as the activation of the Akt/mTOR pathway. The upregulation of SIRT1, PGC-1α, and AMPK, along with inhibition of the Akt/mTOR pathway, promotes autophagy, diminishes myocardial hypertrophy, and improves heart failure [ 11 , 19 ]. The treatment of cardiac cells with Ang II results in a decrease in the expression of SIRT3 and autophagy-related proteins and an increase in the mRNA levels of atrial natriuretic peptide and B-type natriuretic peptide.…”
Section: Role Of Sirtuin-induced Autophagy In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of Flt3 induces the activation of many intermediate signal-transduction mediators, determining cell survival, proliferation, differentiation, and metabolism [ 12 ]. Recent studies from ours [ 13 , 14 ] and others [ 15 ] demonstrated a notable augmentation in the expression of Flt3 in hearts subjected to pathological stress, but its physiological functions and pathological significance remain largely unknown. Our previous studies have demonstrated that cardiac pathological stress triggers the expression of Flt3 in cardiomyocytes, and Flt3 activation with its specific ligand (FL) remarkably reversed Angiotensin II or isoprenaline (ISO)-induced cardiac hypertrophy and cardiac adverse remodeling through AMPK/mTORC1/FoxO3a or SIRT1/p53 signaling [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, LAD-induced cardiac remodeling involves cardiomyocyte apoptosis, necrosis, the disorder of mitochondrial morphology and function, as well as the loss in the number of cardiomyocytes [ 17 ]. Nevertheless, all of these insults elicit mitochondrial dynamics imbalance and oxidative stress while reducing the expression of SIRT1 [ 13 ]. Therefore, we conducted these two experimental models to investigate how Flt3 regulates p53-mediated L-OPA1 processing in the cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%